(untitled) (American Journal of Islam and Society, 2011)
The aim of this article is to highlight a conceptual framework of a well-balanced personality in the light of an Islamic point of view. The article begins with an explanation on the nature of human beings as the underlying concept on which the entire assumption of human personality is based. Further discussion will focus on the types of personality ‒ that is, nafs al-ammārah, nafs al-muţmainnah, and nafs al-lawwāmah. In this regard, the spiritual development process is about the continuous effort of the animal soul to subordinate itself to the power of the rational soul.1 Meanwhile, the educational process ‒ in particular, its methods and the curriculum content ‒ is discussed as an element of intervention in developing good personality traits. The exposition of this article’s writing is derived from scholarly and original sources of knowledge ‒ that is, the Holy Qur’ān and the tradition of the Prophet (ṢAAS), as well as the writings of Muslim scholars to verify and elucidate some of the relevant matters.